Size 12 and ready to rock ebook A heather wells mystery. - Cabot, Meg (Heather Wells Mystery, 2012)
After dallying with sexy vampires and ingeniously reinterpreting the Dracula legend (Insatiable, Overbite), #1 New York Times bestseller Meg Cabot is ready to rock 'n' roll once more with Heather Wells. The un-petite assistant New York City college dorm director and sometime sleuth is back in Size 12 and Ready to Rock—a delectable comedy mystery that proves once more that the much beloved author of The Princess Diaries rules in the realm of grown-up women's fiction as well. Heather's got her hands full when a pop star and her reality TV camera crew invade the dorm—bringing with them a summer camp-full of adoring teen admirers—only to have an inconvenient homicide spoil the fun. There's romance, treachery, merry mayhem and music—just the ticket for readers who like to rock out on the hip contemporary singleton fiction of Sophie Kinsella, Jennifer Weiner, and Jane Green.